2018
DOI: 10.14260/jemds/2018/220
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Epidemiological Pattern of Multidrug Resistant Pulmonary Tuberculosis Patients Presenting to a Tertiary Care Centre in Central India

Abstract: BACKGROUNDIn the present scenario, drug resistance is a huge obstacle in managing TB, as it is not only drug resistant, so difficult to treat, but also has huge financial and social burden. Objectives of the study are-1. To study the epidemiological pattern of pulmonary MDR-TB in central part of Madhya Pradesh. 2. To assess the risk factors for pulmonary MDR-TB. MATERIALS AND METHODS226 MDR-TB patients (with in-vitro resistance to rifampicin and isoniazid via line probe assay) presented to MY Hospital, Indore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
1
Order By: Relevance
“…Regardless of the observed major bias of the study, the observed proportion of primary resistance among MDR/RR TB cases is higher than the studies in India [19] and Gondar University, Ethiopia [26] 10.6% and 13% respectively. The reason for the low proportion for the study in Ethiopia might be due to the high-risk categorization of patients for DST during the study period, or the misclassification bias mentioned above or the ongoing transmissions of MDR/RR TB might have increased the proportion of primary cases in the current study.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Regardless of the observed major bias of the study, the observed proportion of primary resistance among MDR/RR TB cases is higher than the studies in India [19] and Gondar University, Ethiopia [26] 10.6% and 13% respectively. The reason for the low proportion for the study in Ethiopia might be due to the high-risk categorization of patients for DST during the study period, or the misclassification bias mentioned above or the ongoing transmissions of MDR/RR TB might have increased the proportion of primary cases in the current study.…”
Section: Discussioncontrasting
confidence: 60%
“…Although MDR TB doesn’t show significant association with HIV co-infection, most of the studies done reveal associations between Primary MDR TB and HIV co-infection in further analysis of the observed results [17] , [18] . Although studies show a higher proportion of MDR-TB among male patients [19] , [20] , female drug resistant TB patients are more likely to have primary DR-TB [21] .…”
Section: Introductionmentioning
confidence: 99%